Functional Family Therapy to Address Teenage Behavior Problems in Theft Cases in LPKA Bandung - Astri Firdasannah; Ihsana Sabriani Borualogo; Sulisworo Kusdiyati (Psikostudia : Jurnal Psikologi, 2024)
Problematic behavior in teenagers is still a serious focus throughout the world, including in Indonesia. Based on data from the Bandung Special Children's Empowerment Institute (LPKA), there was an increase in the number of prisoners from 2019 to 2021. The highest type of violation was theft. Until now, various interventions are still being sought to deal with this problem. One of them is the development of the Functional Family Therapy (FFT) intervention by Sexton and Alexander since 2002 in the United States. Apart from that, testing of the effectiveness of FFT is still being carried out. However, FFT has not been developed in Indonesia. This research aims to create an FFT design to reduce the frequency of problem behavior and the rate of repeated behavior (recidivism) among teenagers in Indonesia. The research and development method is used as a reference for preparing the design. The conclusion from this research is that the FFT program design has been evaluated and can be tested further to reduce the level of problem behavior and adolescent recidivism in LPKA Bandung. The implication is that FFT is a new intervention to handle cases of law violations by teenagers.Perilaku bermasalah pada remaja masih menjadi fokus serius di seluruh dunia, tak terkecuali di Indonesia. Berdasarkan data dari Lembaga Pemberdayaan Khusus Anak (LPKA) Bandung, terjadi peningkatan jumlah tahanan dari tahun 2019 hingga 2021. Jenis pelanggaran tertinggi ialah kasus pencurian. Sampai saat ini masih diupayakan berbagai intervensi untuk dapat menangani masalah tersebut. Salah satunya, pengembangan intervensi Functional Family Therapy (FFT) oleh Sexton dan Alexander sejak tahun 2002 di Amerika Serikat. Selain itu, pengujian efektivitas FFT masih terus dilakukan. Namun FFT belum dikembangkan di Indonesia. Penelitian ini bertujuan untuk membuat rancangan FFT untuk menurunkan frekuensi perilaku bermasalah dan tingkat perilaku berulang (residivis) pada remaja di Indonesia. Metode research and development digunakan sebagai acuan untuk menyusun rancangan. Kesimpulan dari penelitian ini diperoleh rancangan program FFT yang telah dievaluasi dan dapat dilakukan uji coba selanjutnya untuk menurunkan tingkat perilaku bermasalah dan residivis remaja di LPKA Bandung. Implikasinya adalah FFT ini merupakan intervensi baru untuk menangani kasus pelanggaran hukum oleh remaja Di Indonesia.